2016
DOI: 10.1177/0009922815615826
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Failed Newborn Otoacoustic Emissions Hearing Screen

Abstract: Objective To identify any socioeconomic, demographic, neonatal, and perinatal factors that may be associated with failing the otoacoustic emissions (OAE) newborn hearing screen. Study Design A retrospective chart review was performed looking at hearing screens performed on 1272 newborn infants by OAE testing. Socioeconomic, demographic, neonatal, and perinatal factors were reviewed to determine association with failing the OAE newborn hearing screen. Results Our results demonstrate that Hispanic race was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…We found a strong statistically significant association between family history of hearing impairment and failure in the first OAE. In common with our finding, Shahid et al [ 19 ] found on his retrospective chart review that 6 (50.0%) infants out of 12 who have a family history of congenital hearing loss failed the first OAE. On the other hand, just 102 (8.1%) infants out of 1158 without a family history of congenital hearing loss did not pass the test (P = 0.0002).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found a strong statistically significant association between family history of hearing impairment and failure in the first OAE. In common with our finding, Shahid et al [ 19 ] found on his retrospective chart review that 6 (50.0%) infants out of 12 who have a family history of congenital hearing loss failed the first OAE. On the other hand, just 102 (8.1%) infants out of 1158 without a family history of congenital hearing loss did not pass the test (P = 0.0002).…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, Olusanya et al [ 24 ] stated that VD is associated with more than two-fold risk than a CD. On the other hand, Xiao et al [ 35 ] found that 89 (21.0%) CD infants failed the first test out of 423 infants while 74 (7.1%) VD infants out of 1037 failed the test, which means that the rate of failure was 3 fold in CD infants; also Smolkin et al [ 21 ] found that failure rate was 3.2 higher in CD infants compared to VD infants (20.7% vs. 7.1%).Notwithstanding, in our analysis, the difference between CD and VD was not statistically significant with the failure rate of first OAE, which is similar to Güven [ 4 ] and Shahid [ 19 ] findings. On the contrary, previous studies reported that VD is a statically significant risk factor for first OAE failure [ 24 , 34 , 36 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results of that study found a significant association between altered screening and family history for hearing loss as well as the parents' "race". The authors found no significant association between the variables gender, gestational age, birth weight, maternal age, parity, prenatal, type of delivery, risk of hyperbilirubinemia, feeding of the baby, having health insurance and family income with "failure" in the auditory screening (19) .…”
Section: Discussionmentioning
confidence: 90%